Effects of local infiltration of analgesia and tranexamic acid in total knee replacements: safety and efficacy in reducing blood loss and comparability to intra-articular tranexamic acid - Harish Sivasubramanian; Cheryl Marise Peilin Tan; Lushun Wang (Singapore Medical Journal)
Introduction: The use of periarticular (PA) tranexamic acid (TXA) and its efficacy in comparison with intra-articular (IA) TXA have not been well explored in the literature. This retrospective cohort study aimed to compare the effects of IA and PA TXA with analgesic components in reducing blood loss and improving immediate postoperative pain relief and functional outcomes in patients after unilateral primary total knee arthroplasty (TKA). Methods: A total of 63 patients underwent TKA, and they were divided into the IA TXA delivery group (n= 42) and PA TXA delivery group (n = 21). All patients were administered 1 g of TXA. They also received pericapsular infiltration consisting of 0.5 mL of adrenaline, 0.4 mL of morphine, 1 g of vancomycin, 1 mL of ketorolac and 15 mL of ropivacaine. Outcomes for blood loss and surrogate markers for immediate functional recovery were measured. Results: Of the 63 patients, 54% were female and 46% male. The mean drop in postoperative haemoglobin levels in the PA and IA groups was 2.0 g/dL and 1.6 g/dL, respectively, and this was not statistically significant (P = 0.10). The mean haematocrit drop in the PA and IA groups was 6.1% and 5.3%, respectively, and this was also not statistically significant (P = 0.58). The postoperative day (POD) 1 and discharge day flexion angles, POD 1 and POD 2 visual analogue scale (VAS) scores, gait distance on discharge and length of hospitalisation stay were largely similar in the two groups. Conclusion: Our study showed that both IA and PA TXA with analgesic components were equally efficient in reducing blood loss and improving immediate postoperative pain relief and functional outcomes.